Analysis of stunting prevention through communication, information and education with empowerment - Al Humaerah, Maftuha; Rahayu, Mesra; Zainuddin, Zainuddin (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2024)
Introduction: Stunting is a chronic health problem characterized by a child's height being lower than their age standard, often caused by poor nutritional intake and recurrent infections. This research focuses on stunting prevention through Communication, Information, and Education (KIE) with a community empowerment approach. Research Methodology: This type of research is observational analytics with a cross-sectional approach. The research sample consisted of mothers under five who met the inclusion criteria. Data were collected through questionnaires and interviews and then analyzed using the Wilcoxon statistical test. The intervention was carried out by providing education through digital-based KIE media, developed using the Borg & Gall model. Result: The analysis showed a significant improvement in the knowledge and attitude of mothers under five after the intervention. Before the intervention, 74% of mothers had low knowledge about stunting, but after the intervention, this figure dropped to 2%, with 98% of mothers having good knowledge. The mother's attitude also increased from 2% good to 96% good after the intervention. The results of the Wilcoxon test showed a p-value of 0.001 for knowledge and 0.005 for attitude, showing a significant influence of KIE media on stunting prevention. Conclusion: The provision of digital-based KIE with a community empowerment approach has proven to be effective in increasing the knowledge and attitude of mothers under five towards stunting prevention. Implementing KIE is expected to be a sustainable strategy to support the national program in reducing stunting rates. Further research is suggested to compare the effectiveness between the intervention and control groups.